Dampak Kebijakan Perlindungan Data Terhadap Perilaku Konsumen Di Era Digital - Andre Fahreza; Muhammad Aidil Azman Lubis; Nurbaiti Nurbaiti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to qualitatively explore how data protection policies affect consumer behavior in Indonesia's digital ecosystem. Through literature studies and in-depth interviews, it was found that consumers are increasingly aware of the importance of privacy as part of digital identity. Uncommunicative data protection policies trigger resistance in the form of application avoidance and self-control over shared information. However, the privacy literacy gap remains a major obstacle in realizing effective and fair data protection. Therefore, personal data protection must be understood not only as a legal framework, but also as an ethical value that shapes the relationship between consumers, platforms, and the state. This study suggests a multi-level approach through regulation, education, and consumer empowerment to build an inclusive and equitable digital ecosystem.